Social Policy Welfare State Studies: A Systematic Literature Review (SLR) - Hafid, Mariatul Qibtiah; Salahudin; Muhammad Firdaus (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2025)
This study aims to map the study topics in the field of social policy and welfare states to find out the progress of the study of government science because, basically, each country has different problems. The research method applied to this research is a systematic literature review using 116 scientific articles sourced from scopus databases. As for reviewing articles using the Vosviewer application. The research reveals that there are differences in the concept of social policy by governments in different countries, which is based on the fact that each country has a different background. In spite of the differences, the whole country is making an effort to improve the well-being of its people through its social policies. The entire government effort is supported by some important aspects of it, namely action, regulation, and social services, which are the dominant topics in the research findings. The results of this research contribute to the development of science, in particular governance science related to welfare state social policy, which covers the concept of social policy in welfare states and some important aspects that support social policy and welfare state. The limitation of this research is that the article was used only using secondary data that came from the Scopus database, so the research findings could not comprehensively describe social policies and welfare states in the world. So further research needs to use scientific articles that come from other reputable international databases, such as the Web of Science and Dimensions Scholars (Google Scholar).